Reactive Power Optimization for Loss Reduction and Voltage Profile Improvement - Mazzini, Ana Paula; Asada, Eduardo N.; Lage, Guilherme G. (IEEE PES Conference On Innovative Smart Grid Technologies Latin America (Online), 2019)
This paper proposes the resolution of the optimal reactive dispatch (ORD) problem for the combined objective of minimizing active power losses and voltage profile improvement on load buses considering discrete variables and limited the number of control adjustments. The problem is modeled as a multiobjective ORD problem, a resolution strategy which models discrete control variables by a polynomial discretization function and considers limited number of control adjustments is proposed. The proposed solution method is based on transformation of the original mixed integer nonlinear programming (MINLP) problem with mixed continuous, discrete and binary control variables into a nonlinear programming (NLP) problem with only continuous variables. The method has been tested with IEEE test systems with 118 and 300 buses and the success of the proposed strategy has been observed with the resulting high quality solutions with high speed computation.